Model Of A Quality Assurance System Based On ISO 21001:2018 And Its Application In Education - Sutiyono; Agus Zaenul Fitri; As’aril Muhajir (Pondok pesantren As-salafiyah As-Safi'iyyah, 2025)
This article explores the development of a quality assurance system model grounded in ISO 21001:2018 and its practical implementation within educational institutions. ISO 21001:2018 is an internationally recognized standard specifically tailored for Education Organization Management Systems (EOMS), aiming to enhance the effectiveness of educational processes while meeting the needs and expectations of learners and other stakeholders. This study employs a literature review methodology using a descriptive-analytical approach to examine the core principles and operational requirements of the standard. The findings highlight ISO 21001:2018’s emphasis on a process-based management approach, continuous quality improvement, and learner-centered outcomes. Successful implementation of the standard necessitates strong leadership commitment, adequate training of human resources, and the establishment of a sustainable internal evaluation and audit mechanism. By adopting ISO 21001:2018, educational institutions can foster a structured culture of quality that systematically supports improved learning performance and institutional accountability.